Pengaruh Sistem Aplikasi Berbasis Web Etos Terhadap Kinerja Karyawan Operasional Dalam Kegiatan Bongkar Muat pada PT. Prima Nur Panurjwan - Panjaitan, Frengky; Widilestari, Christine; Retian Asfirah, Lia (PPPM Polimarin, 2024)
Loading and unloading operations include the transportation of goods using land transportation. To carry out these freight transportation activities, the method or service procedure requires the availability of appropriate facilities or equipment. Effective and efficient employee performance is needed by a company because that will advance a company. Employees are expected to work more effectively, with easier access to the information needed, and better coordination between teams. This study aims to discuss the effect of the Electronic Terminal Operation System (ETOS) application system on the performance of operational employees in loading and unloading activities at PT Prima Nur Panurjwan and find out employee perceptions of the ETOS application system affecting the performance of operational employees in loading and unloading activities. This research uses quantitative methods, with questionnaire and observation data collection techniques and data analysis patterns using instrument tests, classical assumption tests, simple regression analysis, determination tests, and t tests. The results of this study validate the research hypothesis that there is a significant influence between the ETOS application system on employee performance at PT Prima Nur Panurjwan.